Connecting the organizational incomes and outcomes: a systematic review of the relationship between talent management, employee engagement, and turnover intention - Sinisterra, Luna; Peñalver, Jonathan; Salanova, Marisa (Frontiers in Psychology, 2024)
In a post-pandemic environment, characterized by volatility and uncertainty, organizations need to adapt to it for their survival. Following a systematic review method, the aim of this study is to assess the relationship between talent management practices, employee engagement, and turnover intention. Carried out using PRISMA guidelines, this systematic review includes 43 studies. Results showed a lack of consensus on the talent management concept, definition, and measurement. Also, talent management practices seem to increase employee engagement and decrease turnover intentions. That is, when organizations provide effective talent management practices to employees, they become more engaged and less likely to abandon the company. It is important to highlight the mediating role of engagement in the relation between talent management and turnover intention. Furthermore, the most studied talent management practices for promoting engagement and reducing turnover intention were identified.Regarding control variables, data highlighted the importance of age and organizational tenure in the aforementioned relationships. This review draws attention to the need of designing and implementing talent management practices in an effective way in order to generate a healthy and engaged workforce that is willing to remain in an organization.